PYATAYEVA ANNA DANILOVNA (1906 – 1981) (Scientific journal of the Fergana State University, 2024)
The article is dedicated to the memory of the outstanding geobotanist researcher of Central Asia Anna Danilova Pyataeva. Anna Danilovna worked for many years at the biology department of the Central Asian State University (now the National University of Uzbekistan). She led and participated in many expeditions organized throughout Central Asia.